Analysis of the transition to an innovative economy in developed countries: (on the example of Israel) - Stella Arzumanyan , Shakhlo Davirova, Zokhida Adilova, Nargiza Khujanazarova, Aziza Karimova (International Journal of Advanced Science and Technology, 2020)
It is very difficult to imagine a modern world economy without innovative technologies and goods. The top ten countries in the Global Innovation Index 2019 are Switzerland, Sweden, the United States, the Netherlands, the United Kingdom, Finland, Denmark, Singapore, Germany and Israel, which are the producers of major innovations in the global economy. Among these countries, Israel, which has had a progressive position in innovation development indicators for the last 10 years, is the object of this study.